Kadar Karbohidrat dan Organoleptik Mie Basah Tepung Biji Nangka Dengan Penambahan Kulit Buah Naga Sebagai Pewarna Alami - Khotijah, Siti; , Dra. Aminah asngad, M.Si (2016)
Jackfruit seed are often waste material from jackfruit which have high nutrition value used optimally and only used us waste. This study determine the organoleptic quality and carbohydrate level jackfruit seed flour noodle with the addition peel dragon fruit as natural colour. The methos used in this study is completely randomized design (CRD) Two factor, factor 1 ratio jackfruit seed flour ; wheat flour (30 g, 50 g, 50 g, 30 g, 60 g, 20 g) and factor II dragon fruit peel extracts (0 ml, 5 ml, 10 ml) with three replications. Data was analyzed by using descriptive qualitative and quantitative. The results of carbohydrate level S1P3 (Flour jackfruit seed 30g, wheat flour 50g, peel exstract dragon fruit 10ml) amounted to 31,15 %, while the carbohydrate level lowest in treatment S2P2 (flour jackfruit 50 g, wheat 30 g, skin fruit 5 ml) by 10,58 %. The quality of the best noodle has a red colour, slighty chewy, texsture not lost, taste bit like a rather unpleasant taste. The conclusion show that the noodle with the addition of jackfruit seed flour dragon fruit peel effect on carbohydrate level and organoleptic propertie of the noodle.